2014
DOI: 10.1371/journal.pone.0090193
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Constipation in Hong Kong Adolescents

Abstract: ObjectiveTo examine the association of constipation with exercise, non-exercise physical activity, and sedentary behaviours in Hong Kong adolescents.MethodsIn 2006–2007, 42 secondary schools were randomly selected to participate in the Hong Kong Student Obesity Surveillance (HKSOS) project. A total of 33692 Form 1–7 students (44.9% boys; mean age 14.8, SD 1.9 years) completed an anonymous questionnaire on lifestyle behaviours. Constipation was defined as a frequency of evacuation of less than once every two da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 41 publications
4
32
1
11
Order By: Relevance
“…Sedentary time, including TV viewing, has also been studied in adults, but only a few studies were carried out on childhood constipation. According to the previous data, long sedentary time was associated with constipation in children . Consistent with the literature, in the present study physical inactivity was associated with non‐daily BM, but it differed according to sex.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Sedentary time, including TV viewing, has also been studied in adults, but only a few studies were carried out on childhood constipation. According to the previous data, long sedentary time was associated with constipation in children . Consistent with the literature, in the present study physical inactivity was associated with non‐daily BM, but it differed according to sex.…”
Section: Discussionsupporting
confidence: 92%
“…Some reported that there was no association between physical activity and constipation in children, 27,39 while others noted that insufficient physical activity was related to constipation in children. 40,41 In adults, there have been many reports showing physical inactivity to be associated with constipation. 42,43 De Schryver et al 44 reported that physical activity intervention improved defecation and total colonic transit time in middleaged adults.…”
Section: Physical Activity and Tv Viewingmentioning
confidence: 99%
“…These efforts to integrate mental health care into the general health care system can enhance the provision of psychiatric care to students with physical illnesses [11]. What's more, to highlight the university sports education function and constantly improve the quality and efficiency of sports teaching, various forms and interesting sports teaching methods can be adopted and university sports education courses should be promoted to students.…”
Section: Implications For Future Health Education In University Townsmentioning
confidence: 99%
“…Moreover, few studies had been conducted about the topic. Qualitative methods had been adopted in this research to obtain more detailed information [11].…”
mentioning
confidence: 99%
“…Physical exercise is the realization of movements of the body and its parts by means of muscular contractions resulting in a muscle energy expenditure greater than the expense of energy at rest [1]. It is often confused with the term sport and in this orientation,physical exercise includes all physical activities and sports activities with specific objectives for each category.…”
Section: Introductionmentioning
confidence: 99%